2007
DOI: 10.4049/jimmunol.179.5.3196
|View full text |Cite
|
Sign up to set email alerts
|

A Streptococcal Penicillin-Binding Protein Is Critical for Resisting Innate Airway Defenses in the Neonatal Lung

Abstract: Group B streptococcus (GBS) is a major cause of neonatal pneumonia. The early interactions between innate airway defenses and this pathogen are likely to be a critical factor in determining the outcome for the host. The surface-localized penicillin-binding protein (PBP)1a, encoded by ponA, is known to be an important virulence trait in a sepsis model of GBS infection that promotes resistance to neutrophil killing and more specifically to neutrophil antimicrobial peptides (AMPs). In this study, we used an aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…As is true in Staphylococcus aureus, mutation of the dlt system results in alteration of surface-expressed LTA, an increase in the overall surface negative charge, and increased susceptibility of GBS to antimicrobial peptides (Poyart et al, 2003). Deletion of penicillin-binding protein 1A (product of the ponA gene) results in increased susceptibility of GBS to antimicrobial peptides and in decreased virulence in a rat model of GBS sepsis and pneumonia (Hamilton et al, 2006;Jones et al, 2007). Deletion of pilB, one of the GBS pilus-forming proteins, was shown to result in increased susceptibility to neutrophil and antimicrobial peptide killing, and decreased virulence in a mouse model of GBS sepsis (Maisey et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…As is true in Staphylococcus aureus, mutation of the dlt system results in alteration of surface-expressed LTA, an increase in the overall surface negative charge, and increased susceptibility of GBS to antimicrobial peptides (Poyart et al, 2003). Deletion of penicillin-binding protein 1A (product of the ponA gene) results in increased susceptibility of GBS to antimicrobial peptides and in decreased virulence in a rat model of GBS sepsis and pneumonia (Hamilton et al, 2006;Jones et al, 2007). Deletion of pilB, one of the GBS pilus-forming proteins, was shown to result in increased susceptibility to neutrophil and antimicrobial peptide killing, and decreased virulence in a mouse model of GBS sepsis (Maisey et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Much of what is known about GBS virulence has been defined in animal models of systemic infection (18,20,23,25,28,46,47). GBS has also been described in animal models of localized colonization and infection, including vaginal (7,8), pulmonary (15,19,22), mammary (52), and orogastric (27) infection models. GBS can also cause cystitis and pyelonephritis (54,55), but the urinary tract is less well characterized as a site of GBS-host interactions.…”
mentioning
confidence: 99%
“…There appears to be functional redundancy in PBP activity such that inactivation of one PBP can often be compensated for by others [25][26][27][40][41][42][43]. We have previously shown that PBP1a is important for virulence of GBS in neonatal rat pups, both in an intraperitoneal sepsis model [21,22] and in lung colonization model [23].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that PBP1a, a surface-localized penicillin-binding protein encoded by ponA, plays an important role in the pathogenesis of GBS infection as a mutant lacking PBP1a is attenuated for virulence in a neonatal rat sepsis infection model [21,22] and cleared more rapidly from the lungs of neonatal rat pups in an aerosol infection model [23]. Additional characterization of the mutant revealed that PBP1a promotes resistance of GBS to killing by host innate immune antimicrobial peptides, which likely contributes to the virulence defect of this mutant [24].…”
Section: Introductionmentioning
confidence: 99%